2021
DOI: 10.3991/ijet.v16i23.27825
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effect of Immersive English Teaching

Abstract: Immersive teaching has achieved remarkable results in bilingual learning. This teaching method creates an immersive environment for learners to understand and use languages. This paper explores the influence of immersive teaching on the learning performance, interest, and satisfaction of Chinese English learners, and provides several suggestions on how to apply immersive teaching. The results show that immersive teaching improves the listening, speaking, reading, and writing abilities of students. One semester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…According to the trends of teaching and learning nowadays, it is inevitable that online is one of the essential channels to manage teaching and learning processes [11]. Thus, the way the teacher gives feedback has simultaneously adjusted.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the trends of teaching and learning nowadays, it is inevitable that online is one of the essential channels to manage teaching and learning processes [11]. Thus, the way the teacher gives feedback has simultaneously adjusted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been several research investigating the benefits of utilizing Zoom meeting applications. With regards to the study conducted by [11], it has been found that the basic problem of learning through Zoom applications was the failure of internet networks, limited features of online learning applications, and obstacles in terms of learning services. These similar drawbacks have also been found specifically in the research performed by using Zoom meeting application in speaking skills class [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been, also, reported that young adults could perform academic task better if they learnt through the internet, meaning that acquiring knowledge in a formal classroom will be less likely effective than that of conducting in the virtual classroom [2]. The youth report also shared the feeling of not being up to date from academic learning when teachers failed to spend their funds of knowledge of digital literacies [3]. Thereby, some of the virtual worlds like VRChat have offered a promising context for academic learning where multiple users are able to interact in a shared space in real time by creating motional characters.…”
Section: Introductionmentioning
confidence: 99%